Changes in Sleep in Pregnant Women During Covid-19 Pandemic - Ruris Haristiani; Nur Al Marwah Asrul; Yusmar Yusuf (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Covid-19 Pandemic has an impact on human health and wellbeing. Psychological distress and changes in routine during lockdown led to changes in sleep habits and sleep quality. This systematic review aimed to examine pregnant women's sleep change during the Covid-19 outbreak. In December 2021, there were six electronic databases for articles published by 2019 (the first covid-19 outbreak) to 2021 (PubMed, Research Gate, Science Direct, ProQuest, Sage, and Google scholar). The search yielded 1846 unique articles, 6 of which were eligible. Most of the articles did observations, interviews, and questionnaires on pregnant women. Of six works of literature selected, four indicated a positive correlation between the pandemic Covid-19 and sleep disorders in pregnant women, while two suggested the opposite results. Sleep changes experienced were varied, such as getting late bedtime, shortening in sleep duration, worsening sleep quality, and even respondents who rarely sleep.